KEARIFAN LOKAL DIPLOMASI DENGAN ROH HALUS DALAM CERPEN “PERTEMUAN DENGAN ROH HALUS” KARYA W.S RENDRA - I Ketut Sudewa (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
In the short story “Peremuan Dengan Roh Halus”, W.S Rendra revealed about the local wisdom of the Wonogiri community in Central Java and W.S Rendra's views on this local wisdom. This was conveyed by a unique story technique, namely the storytelling technique. This local wisdom can be a medium of learning in recognizing various local wisdoms that exist in Indonesian society. By knowing and understanding various local wisdoms that exist in Indonesia, it is hoped that they can become a glue and unifier of the nation, especially in maintaining the nation's culture which is known to be very good. This study discusses the local wisdom contained in the short story